1957
DOI: 10.1113/jphysiol.1957.sp005834
|View full text |Cite
|
Sign up to set email alerts
|

Fate and excretion of the pressor activity of vasopressin in rats

Abstract: The fate of the antidiuretic activity of vasopressin has been investigated in experiments in vivo (Burn & Singh Grewal, 1951;Heller, 1952Heller, , 1953Ginsburg & Heller, 1953;Dicker, 1954;Dicker & Greenbaum, 1954) and in experiments in vitro (Heller & Urban, 1935;Birnie, 1953;Dicker & Greenbaum, 1956). The antidiuretic activity of vasopressin appears to be inactivated by both liver and kidneys though the manner in which the inactivation takes place is still not clear. As for the metabolism of the pressor activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

1958
1958
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Thus, in newborn rats deprived of milk for 24 h, the quantity of hypophysial ADH decreases (17). This is not the case for adult rats deprived of water for 4 days (13). In addition, in adult rabbits, a hypophysial ADH depletion of 30 % appears only after 7 days of water deprivation (24).…”
Section: Discussionmentioning
confidence: 88%
“…Thus, in newborn rats deprived of milk for 24 h, the quantity of hypophysial ADH decreases (17). This is not the case for adult rats deprived of water for 4 days (13). In addition, in adult rabbits, a hypophysial ADH depletion of 30 % appears only after 7 days of water deprivation (24).…”
Section: Discussionmentioning
confidence: 88%
“…Several years ago Heller (1939) had already noted a difference between the stability of both pressor and antidiuretic activities. A difference in the metabolism of the antidiuretic and the pressor activities of Pitressin injected in vivo has also been postulated more recently by Dicker & Nunn (1957). In a pilot experiment, during which vasopressin had been incubated with cysteine and assayed simultaneously for its antidiuretic and pressor activities, it was found that while there was no decrease of the pressor activity, the antidiuretic activity was reduced by one third.…”
Section: Discussionmentioning
confidence: 94%
“…Vasopressin injected intravenously disappears rapidly from the blood (O'Connor, 1951;Dicker & Nunn, 1957;Heller & Zaidi, 1957). When 1 unit LVP was admini¬ stered subcutaneously, an amount approximately equivalent to that discharged by the posterior pituitary after stalk lesion, almost no influence on water intake and urine output was seen.…”
Section: Discussionmentioning
confidence: 99%